Синтез робастных систем компенсации искажений магнитного поля - Розов, В. Ю.; Кузнецов, Б. И.; Пелевин, Д. Е. (Видавництво Львівської політехніки, 2011)
The robust systems synthesis method of geomagnetical field and industrial frequency magnetic-field of distortions indemnification by means of magnetic-field guided sources in man protracted stay areas is worked out. An example of the synthesized system is given.
Keywords: distortions of magnetic-field; system of indemnification; robust control